Research Progress of Serological Markers Related to Infection in Acute Pancreatitis - Tan, Quanxin; Qiao, Min (Journal of Contemporary Medical Practice, 2025)
Acute pancreatitis (AP) is a common acute abdominal disease in clinical practice. Its essence is a chemical inflammation. However, during its occurrence and development, it is often accompanied by infection in or around the pancreas. The severity of infection is of great significance for judging the severity of acute pancreatitis. In recent years, some infection-related serological markers have been used to assist in judging the severity of acute pancreatitis. This article reviews the research progress of infection-related serological markers in predicting the severity and prognosis of acute pancreatitis.